Fabrication and Compact Modeling of Low-Voltage Flexible Organic TFT Using Self-Assembly of Conductive Polymer Channel Over High-k PMMA/SrZrO Dielectric - Singh Mehrolia M.; Kumar D.; Verma A.; Kumar Singh A. (My University, 2025)
This article describes a comprehensive study of fabrication, characterization, and compact modeling of the organic thin-film transistor (OTFT) that can find a variety of applications for the development of future-generation flexible and transparent circuits. Furthermore, these flexible and partial transparent devices are working at low operation voltage that can also cater to the need for low power requirements. Here, the PBTTT-C14 (conductive polymer) is used as an active semiconductor channel and polymer dielectric/inorganic oxide blend (PMMA and SrZrOX) based hybrid dielectric) used as a gate oxide layer. The low-cost, minimal wastage floating film transfer (FTM) method and spin coating method are used to deposit the layer of organic semiconductor (OSC) channel and hybrid dielectric, respectively. The deposited dielectric thin film over the ITO-coated flexible substrate has been cured with UV processing, which has the advantage of a high-quality film with low-temperature processing steps. The atomic force microscopy (AFM) image of the dielectric film shows a uniform smooth (very low roughness σrms = 0.407 nm), confirming that the thin film passes with the very low number of surface defects, which is suitable for high-quality transistors. Meanwhile, the deposited organic semiconductor film using FTM is uniform and free from any anisotropy. The developed organic TFT has the ability to operate at a low voltage of -1.0 V and offers a high ION/IOFF ratio of -0.5×105 and a low threshold of -0.27 V and can be utilized in portable sensors and wearable and flexible electronic applications. The compact modeling of the device has been done to further analyze the performance of the OTFT-based inverter circuits. © 1963-2012 IEEE.